Prevalence and clinical presentation of Rickettsia, Coxiella, Leptospira, Bartonella and chikungunya virus infections among hospital-based febrile patients from December 2008 to November 2009 in Bangladesh. Issue 1 (December 2017) - Faruque, Labib; Zaman, Rashid; Gurley, Emily; Massung, Robert; Alamgir, A.; Galloway, Renee; Powers, Ann; Bai, Ying; Kosoy, Michael; Nicholson, William; Rahman, Mahmudur; Luby, Stephen
Abstract Background We conducted a study to identifyRickettsia, Coxiella, Leptospira, Bartonella, and Chikungunya virus infections among febrile patients presenting at hospitals in Bangladesh. Methods We collected blood samples from patients at six tertiary hospitals from December 2008 to November 2009 and performed laboratory tests at the United States Centers for Disease Control and Prevention (CDC). Results Out of 720 enrolled patients, 263 (37%) were infected withRickettsia; 132 patients had immunofluorescence antibody titer >64 against spotted fever, 63 patients against scrub typhus fever and 10 patients against typhus fever. Ten patients were identified withCoxiella . We isolatedLeptospira from two patients andBartonella from one patient. Ten patients had antibodies against Chikungunya virus. The proportion of patients who died was higher with rickettsial fever (5%) compared to those without a diagnosis of rickettsial infection (2%). None of the patients were initially diagnosed with rickettsial fever. Conclusions Rickettsial infections are frequent yet under-recognized cause of febrile illness in Bangladesh. Clinical guidelines should be revised so that local clinicians can diagnose rickettsial infections and provide appropriate drug treatment.